OVERVIEW OF SANITATION HYGIENE AND BACTERIOLOGICAL QUALITY OF FOOD AND EQUIPMENT ON FOOD MANAGEMENT SITES AT JUANDA AIRPORT, SURABAYA IN 2019 - Devi Shintiya Chilmi; Ririh Yudhastuti; Bangun Cahyo Utomo (Universitas Airlangga, 2021)
ABSTRACTSites for managing and providing food for the community contribute to the emergence of major foodborne diseases. The airport gives notes on how important it is to prevent food-borne diseases. This study aimed to review the sanitary hygiene and bacteriological quality of the food and equipment on food management sites in Terminal 1 of Juanda Airport, Surabaya. This was a descriptive study using a cross-sectional study design. The research population was all 53 food management sites in Terminal 1 of Juanda Airport. A large sample of four food management sites were taken based on the number of food management sites offered to be surveyed every month. The research variables were sanitation hygiene and bacteriological quality of the food and equipment on the food management sites. Data collection on sanitation hygiene was done through observation and interview. Data collection on bacteriological quality of food and equipment was performed by taking and checking food samples and equipment from each food management site. The assessment of sanitation hygiene on the four food management sites in Terminal 1 of Juanda Airport received a score of > 700. The results of bacteriological food quality showed that Escherichia coli was found in food samples produced by one food management site. The results of bacteriological equipment quality showed that there was no Escherichia coli on the equipment used by four food management sites, but the total plate count value on the equipment was > 0. All food management sites in Terminal 1 of Juanda Airport met sanitation hygiene requirements but did not meet the bacteriological quality requirements for equipment because the total plate count value exceeded the threshold value. In terms of bacteriological food quality, most of the food management sites met the health requirements. Keywords: sanitation and hygiene, Escherichia coli, total plate count, airports